2022
DOI: 10.1108/ijdi-03-2022-0047
|View full text |Cite
|
Sign up to set email alerts
|

Economic complexity and entrepreneurship: insights from Africa

Abstract: Purpose Economic complexity reflects the nature of knowledge accumulated and technological capability of a nation. This study aims to evaluate the impact of economic complexity on entrepreneurship in selected African countries. Design/methodology/approach The study uses country’s level data of 18 countries covering a period of 2006–2017. Data are sourced from Massachusetts Institute of Technology’s Observatory of Economic Complexity database, World Bank’s Entrepreneurship Database and World Development indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 80 publications
1
19
1
2
Order By: Relevance
“…Rubbo et al (2021) confirmed that innovation and economic complexity have significant effects on firm productivity in BRIC nations. Contrary to Nguyen et al (2021), the study of Ajide (2022) did not confirm a nonlinear relationship between entrepreneurship and economic complexity.…”
Section: Literature Review and Hypothesis Developmentcontrasting
confidence: 66%
See 4 more Smart Citations
“…Rubbo et al (2021) confirmed that innovation and economic complexity have significant effects on firm productivity in BRIC nations. Contrary to Nguyen et al (2021), the study of Ajide (2022) did not confirm a nonlinear relationship between entrepreneurship and economic complexity.…”
Section: Literature Review and Hypothesis Developmentcontrasting
confidence: 66%
“…They suggest that after a certain threshold, economic complexity may reduce entrepreneurship, possibly due to the saturation of the entrepreneurs in the system, which lead to highly competitive forces. This action creates a potential threat to latent entrepreneurs and suppresses the inflow of new business creation (Ajide, 2022). The coefficient of economic growth was negative and significant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations